Determine the Risk Level of Occupational Hazards among Laboratories Staffs in Makkah among Laboratories Staffs in Makkah - Almutair, Nayef Shabbab; Vivien How,, Shamsul Bahri Bin Md Tamrin, Ng Yee Guan, (Opción, 2019)
This study aimed to determine the risk level of occupational hazards (chemical, physical, biological, ergonomic) among laboratories staffs in Makkah via hazard identification risk assessment and risk control (HIRARC). These results indicated that the severity of risk and control measures related to chemical hazards showed that only 53.3% had a low risk while 46.7 were at a moderate level. As a conclusion, the majority of laboratories staff were in the high level of risk related to occupational hazards and it shows the need for control of this issue and finds a practical way to solve this problem.